Determinants of stroke among adult hypertension patients in dessie comprehensive specialized hospital and Kombolcha general hospital, Amhara, Ethiopia: A case-control study. - Muluken Demile; Molla Kassie Yenesew; Abebe Bekele Jibat; Yohannes Kibret; Dagnachew Melak; Endalew Minwuye Andargie; Yonas Fissha Adem (PLoS ONE)
Introduction Despite the increased admission of stroke patients in hospitals as a result of hypertension, especially in Ethiopia, there are limited studies that aim to explore important determinants of stroke, mainly among adult hypertensive patients. Therefore, this study was conducted to identify determinants of stroke among adult hypertension patients in Dessie Comprehensive Specialized Hospital and Kombolcha General Hospital, Amhara, Ethiopia. Methods An institutional-based case-control study design was conducted at Dessie Comprehensive Specialized Hospital and Kombolcha General Hospital from April 10, 2023, to May 30, 2023, on 105 cases and 420 controls selected by using a systematic random sampling technique. Data entry and processing were done using EPI-data version 4.4.2 and exported to SPSS version 26.0 for further analysis. Bi-variable and multi-variable logistic analysis was done to identify determinants of stroke among hypertension patients. Data were interpreted by using the odds ratio with a 95% confidence level, and a P-value < 0.05 was taken as statistically significant. Results A total of 105 cases and 420 controls participated in this study with a complete response (100%). Stroke among adult hypertension patients was significantly associated with a family history of hypertension (AOR =  2.8, 95% CI: 1.8-4.3), being physically inactive (AOR =  2.13, 95% CI: 1.4-3.3), current smoking cigarettes (AOR =  3.2, 95% CI: 2.1-5.2), current alcohol drinking (AOR =  4.7, 95% CI: 2.87-7.9), and having heart disease (AOR =  2.04, 95% CI: 1.3-3.25). Conclusions Having a family history of hypertension, cigarette smoking, physical inactivity, alcohol consumption, and heart disease were determinants of stroke. Health education on lifestyle practices, early hypertension, and other cardiovascular diseases in each follow-up visit is very essential for improving stroke prevention.